Broadband electromagnetic dipole scattering by coupled multiple nanospheres. (November 2017) - Jing, Xufeng; Ye, Qiufeng; Hong, Zhi; Zhu, Dongshuo; Shi, Guohua
Abstract: With the development of nanotechnology, the ability to manipulate light at the nanoscale is critical to future optical functional devices. The use of high refractive index dielectric single silicon nanoparticle can achieve electromagnetic dipole resonant properties. Compared with single nanosphere, the use of dimer and trimer introduces an additional dimension (gap size) for improving the performance of dielectric optical devices through the coupling between closely connected silicon nanospheres. When changing the gap size between the nanospheres, the interaction between the particles can be from weak to strong. Compared with single nanospheres, dimerized or trimeric nanospheres exhibit more pronounced broadband scattering properties. In addition, by introducing more complex interaction, the trimericed silicon nanospheres exhibit a more significant increase in bandwidth than expected. In addition, the presence of the substrate will also contribute to the increase in the bandwidth of the nanospheres. The broadband response in dielectric nanostructures can be effectively applied to broadband applications such as dielectric nanoantennas or solar cells. Highlights: The use of dimer and trimer nanospheres introduces the coupling interaction between nanoparticles with smaller gap. Compared with single nanospheres, the dimer or trimer nanospheres exhibit more pronounced broadband scattering properties. The presence of the substrate can contribute to the increase of the bandwidth of electromagnetic dipole scattering.